2010
DOI: 10.1177/1043454210364623
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Experiences of What Comforts Them When Their Child is Suffering From Cancer

Abstract: The aim of the study was to describe parents' narratives concerning what they find comforting when they have a child suffering from cancer. Interviews were conducted with 9 parents--8 mothers and 1 father--of children aged 3 to 9 years who were admitted to a pediatric oncology ward and had undergone their first treatment. The findings showed that the parents derived comfort from being close to their child, perceiving the child's strength, feeling at home in the ward, being a family and being at home, and recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
69
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(77 citation statements)
references
References 31 publications
(39 reference statements)
6
69
0
2
Order By: Relevance
“…Apart from this, leaving the sick child at the hospital to return to the rest of the family did not come across as an option for the mothers. This concurs with the findings of Ångström-Brännström et al 21 who found that parents gained comfort when they were physically and emotionally close to the sick child.…”
Section: Impact On Mothers Occupational Rolessupporting
confidence: 79%
“…Apart from this, leaving the sick child at the hospital to return to the rest of the family did not come across as an option for the mothers. This concurs with the findings of Ångström-Brännström et al 21 who found that parents gained comfort when they were physically and emotionally close to the sick child.…”
Section: Impact On Mothers Occupational Rolessupporting
confidence: 79%
“…Nurses, who developed a close relationship with parents and turned their attention to the whole family, comforted parents. Parents were also relieved through practical help, kindness and thoughtfulness from their social network (14). Parents of children treated for cancer spoke about the comfort they received from other families and caregivers on the ward (15).…”
Section: Comfort For Comforters In Pediatric Palliative Carementioning
confidence: 99%
“…In 2005-2006 a study about the comforting of children undergoing cancer treatment was carried out at a pediatric oncology ward in northern Sweden (14). A 9 year old boy relapsed and CÅB met regularly with him and his family and made field notes at the hospital (22).…”
Section: Procedures and Data Collectionmentioning
confidence: 99%
“…7,9 Parents of children with cancer cared for at home and in hospitals emphasized that they could relieve distress for their children by being present during treatment. 10,11 Parents are described as bridges between nurses and children, and nurses can empower parents to help them comfort their children. 10,11 As far as we know, comfort has not been studied simultaneously from the perspective of a child and the child's parent and nurse.…”
mentioning
confidence: 99%
“…10,11 Parents are described as bridges between nurses and children, and nurses can empower parents to help them comfort their children. 10,11 As far as we know, comfort has not been studied simultaneously from the perspective of a child and the child's parent and nurse. The aim of this study was to describe a child's experiences while being treated for cancer until death as narrated by the child and his mother and nurse, with the focus on discomfort and comfort while all being observed by a researcher.…”
mentioning
confidence: 99%